Cloning of a new form of EAAT2/GLT-1 from human and rodent brains. (29th May 2022) - Lee, A.; Klinkradt, S.; McCombe, P.A.; Pow, D.V.
Highlights: We have cloned a new variant of GLT-1, which we call GLT-1d that varies at its C-terminus as a consequence of alternate RNA splicing. The 5′ end of GLT-1d mRNA can also be alternatively spliced. GLT-1d is a functional glutamate transporter and contains a putative class II PDZ binding motif that is absent in GLT-1a (the originally described, predominant brain form). RT-PCR reveal that GLT-1d message was present not only in brain, spinal cord and astrocyte cultures, but also in retina and some peripheral organs, including liver and testis, indicating a potentially widespread functional role. Abstract: Glutamate transporter 1 is the principal transporter that mediates glutamate clearance in the mammalian brain. In rodents, it is referred to as GLT-1, whereas in humans it is referred to as EAAT2. We have cloned a novel and abundantly expressed carboxyl-terminal splice variant of this transporter in both rodents and humans, which we denote as GLT-1d/EAAT2d. The novel splice variant results from usage of internal splice sites and the splicing event leads to novel extra sequence spliced in after exon 10. The open reading frames of GLT-1d and EAAT2d encode proteins of 572 and 566 amino acids respectively; both contain a C-terminal PDZ motif. When expressed in COS7 cells, the proteins function as glutamate transporters that are inhibited by dihydrokainate (a GLT-1/EAAT2 transporter inhibitor). RT-PCR amplification using GLT-1d specific primers confirmed expression of message in all brain regions examined (forebrain, midbrain, hindbrain and cerebellum) as well as spinal cord, astrocyte cultures, retina and peripheral tissues (liver, testis, small intestine and lung). Quantitative RT-PCR analysis showed that expression of GLT-1d is developmentally regulated. In adult human brain, EAAT2d message is ∼ 30% of the level of EAAT2a message (the most abundant form), potentially making it the second most abundantly expressed form of EAAT2 in the brain. The amino terminal region of GLT-1d is also alternately spliced; the brain and testis forms contain a sequence corresponding to the amino acid sequence MASTEG whereas the corresponding liver sequence is MVS. In summary, we have cloned a novel EAAT2/GLT-1 splice variant from human and rodent brains. The splice variant is abundantly expressed in the brain, spinal cord, retina, liver and testis; it is a functional glutamate transporter; therefore, we conclude that it will likely have a functional role in glutamate homeostasis in the rodent and human nervous system, during development, adulthood, and plausibly in pathological states.